Special economic zones and the influence of transport modes: proposal of a theoretical model appropriate to the brazilian reality: PROPOSAL OF A THEORETICAL MODEL APPROPRIATE TO THE BRAZILIAN REALITY - Valim , Lucas Maiolini; Frogeri, Rodrigo Franklin; Camarini, Gladis (Perspectivas Contemporâneas, 2024)
Special Economic Zones (SEZs) have become in recent decades an important strategy for economic stimulation. The SEZs are associated with regional development policies and the fight against economic stagnation. The effectiveness of a SEZ depends on the regional economic context, its potential, incentive policies and investment attraction, as well as the supply of infrastructure for productive development. Thus, this study aims to establish a theoretical/hypothetical relational model that represents the influence of transport modes on the effectiveness of a regional development strategy of the SEZ type. To reach the proposed objective, an extensive Systematic Literature Review was carried out with the help of the scientific platforms Connected Papers and Ryyan, aligned with research in the main academic databases (Scopus, Web of Science, EBSCO host, ieeeXplore, Emerald insight). A qualitative approach, inductive logic, and interpretivist epistemology were adopted. The results of the study suggest a theoretical/hypothetical model composed of eight hypotheses and nine constructs (factors that enable SEZ effectiveness, factors that compromise the SEZ effectiveness, SEZ effectiveness, modals of transport, SEZ performance, SEZ program, SEZ characteristics, contextual factors and regional development. The study improves the regional development literature and especially the Special Economic Zones theme by establishing solid theoretical relationships among the suggested constructs.